Himpunan petunjuk teknis pelaksanaan proyek-proyek Direktorat Jenderal Bina Rehabilitasi Sosial, tahun 1984/1985 (Departemen Sosial R.I. Direktorat Jenderal Bina Rehabilitasi Sosial, 1984)
On the social rehabilitation of the handicapped, juvenile delinquents, etc.; a guide to the projects of the Directorat Jenderal.